PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT ULU IDANOTAE KABUPATEN NIAS SELATAN - Herisokhi Giawa (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
This study utilizes an associative quantitative research approach with the objective of exploring the correlation between variables, specifically focusing on cause and effect relationships. It was carried out at the Ulu Idanotae Subdistrict Office, situated in South Nias Regency, with a sample size consisting of 32 employees. The analysis of data, conducted through partial statement items, reveals that the leadership style variable exhibits a statistically significant positive impact on employee performance, as evidenced by a t-value of 7.784, surpassing the critical value of 1.697, with a significance level of 0.036, which is greater than the threshold of 0.05. Similarly, regarding work discipline, the t-value is 2.309, exceeding the critical threshold of 1.697, with a significance level of 0.28, indicating no statistically significant impact on employee performance. Consequently, it can be inferred that both leadership style and work discipline variables play a role in influencing employee performance. Furthermore, when examined collectively, the variables of leadership style and work discipline significantly affect employee performance at the Ulu Idanotae sub-district office, South Nias district, with an F value of 37.630, surpassing the critical value of 1.697, and a significance level of 0.054, which is higher than 0.05.